Auto-organização de colóides magnéticos anisotrópicos em campos oscilantes - Freitas, Everton Almeida de (2018)
A two-dimensional system of magnetic colloids with anisotropic geometry (rods) subjected to an oscillating external magnetic field is studied in this work. Specifically, the structural and dynamical properties (diffusion and synchronization) of the self-organized configurations are analyzed as a function of the misalignment of the intrinsic magnetic dipole moment of the rods with respect to their axial direction, and also as a function of the intensity and frequency of oscillation of the external magnetic field. The system is studied by means of Langevin Dynamics simulations. The misalignment of the dipole, relative to their axial direction, is inspired by recent experimental and theoretical studies, and this fact is relevant in the microscopic aggregation states of the system. For example, solid structures can be observed in systems whose magnetic moments are arranged perpendicular to the axis of the colloidal rod, which contrasts with the liquid state found when a small misalignment is considered. In addition, the dynamic response of the magnetic rods to the oscillating external magnetic field is strongly affected as a function of this characteristic. Regarding the synchronization between the direction of the magnetic colloids and the direction of the external magnetic field, it is observed that the its intensity and frequency of oscillation are important parameters, which define very distinct regimes of synchronization. A set of phase diagrams are presented, showing in what intervals the intensity and frequency of oscillation of the external magnetic field the different self-organized structures can be observed.